PELAKSANAAN PEMBELAJARAN INKUIRI TERBIMBING MUATAN IPA PADA SISWA KELAS V DI SDN 004 SUNGAI KUNJANG - Agustin, Yuli; Sunarno, Sunarno; Kusdar, Kusdar (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, 2021)
This study aims to determine the implementation of learning using the science content inquiry learning model in fifth grade students of SD Negeri 004 Sungai Kunjang. The background of this research is that science learning in class V SD Negeri 004 Sungai Kunjang is still relatively low. This study uses qualitative research with the subject of class V SD Negeri Sungai Kunjang. In collecting data the researchers used the methods of observation, interviews, and documentation. Data analysis techniques used are data reduction, data display, and drawing conclusions. To test the validity of the data used credibility test with triangulation technique. Based on the results of the research, planning for inquiry learning in class V SDN 004 Sungai Kunjang in planning learning the teacher makes or designs learning by making lesson plans that will be implemented. In making the RPP the teacher is said to be good because in making the RPP the teacher has included the steps of inquiry learning. The implementation of inquiry learning in class V SDN 004 Sungai Kunjang is said to be good because the teacher carries out learning according to the steps of inquiry learning. In addition to the teacher making lesson plans, the teacher also plans to make group work sheets (LKK) and student worksheets (LKS). In making LKS the teacher determines the main questions that are in accordance with the learning material. In the evaluation of inquiry learning the teacher evaluates using process evaluation and evaluation of results that make it easier for teachers to evaluate the inquiry learning.